2009
DOI: 10.1073/pnas.0911782106
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor RORα exerts a bi-directional regulation of IL-6 in resting and reactive astrocytes

Abstract: Astrocytes and one of their products, IL-6, not only support neurons but also mediate inflammation in the brain. Retinoidrelated orphan receptor-␣ (ROR␣) transcription factor has related roles, being neuro-protective and, in peripheral tissues, antiinflammatory. We examined the relation of ROR␣ to astrocytes and IL-6 using normal and ROR␣ loss-of-function mutant mice. We have shown ROR␣ expression in astrocytes and its up-regulation by pro-inflammatory cytokines. We have also demonstrated that ROR␣ directly tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…Similar findings have also been mentioned in astrocytes, where Rev-erb␣ competes with ROR␣ for the up-regulation of IL6 in NF-B-dependent pathway (35). Rev-erb␣ competition with ROR␣ on IL6 gene promoter, however, has been shown to repress IL6 (35,36).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar findings have also been mentioned in astrocytes, where Rev-erb␣ competes with ROR␣ for the up-regulation of IL6 in NF-B-dependent pathway (35). Rev-erb␣ competition with ROR␣ on IL6 gene promoter, however, has been shown to repress IL6 (35,36).…”
Section: Discussionsupporting
confidence: 67%
“…3C). Earlier studies have mentioned Rev-erb␣ in the bidirectional regulation of cytokine IL6 as well as in modulation of IL10, which implies that its role is as an equilibrist (35,36). Also, due to observed antimicrobial effects in Rev-erb␣-overexpressing cells, oxidative stress in MDMs overexpressing Rev-erb␣ was monitored by a DHR123 assay, which indicated significant change in reactive oxygen species (supplemental Fig.…”
Section: Rev-erb␣ Modulation Of Antimycobacterial Response Of Macrophmentioning
confidence: 99%
“…Thus, we surmise that clock dysfunction is in part responsible for increased proinflammatory gene expression in smokers and patients with COPD. This assertion is supported by the findings that core clock proteins (e.g., REV-ERBa) accumulate on the promoters of proinflammatory genes including IL-6, thereby inhibiting expression (5,7,38). Further study is required to determine if recruitment of core clock proteins and nuclear receptors to proinflammatory genes is altered in smokers and patients with COPD as compared with nonsmokers.…”
Section: Original Researchmentioning
confidence: 66%
“…One candidate is IL-6 (interleukin-6), a cytokine that can promote neuronal survival. We previously demonstrated that ROR␣ modulates its expression by astrocytes (Journiac et al, 2009). Alternatively, ROR␣-deficient astrocytes may secrete larger amounts of factors toxic to neurons, such as NO.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, ROR␣ is expressed in neurons in the cortex, cerebellum, inferior olivary nucleus, hippocampus, thalamus, hypothalamus, olfactory bulb, and retina (Ino, 2004). We also recently reported the nuclear expression of ROR␣ in astrocytes, particularly in the hippocampus, cortex, and cerebellum (Journiac et al, 2009). There is a natural mutant mouse for ROR␣, called staggerer, which carries a 122 bp deletion in the ligand-binding domain (LBD) of the Rora gene (Hamilton et al, 1996).…”
Section: Introductionmentioning
confidence: 99%